Simulation Study on the Effect of Forced Ventilation in Tunnel under Single-Head Drilling and Blasting - Qingsong Pu; Yi Luo; Junhong Huang; Yingwei Zhu; Shaohua Hu; Chenhao Pei; Guang Zhang; Xinping Li (Shock and Vibration)
Based on the excavation of Yuelongmen tunnel on ChengLan Railway in China, this paper will probe into the forced ventilation effect of harmful gas generated by drilling and blasting construction, simulate the diffusion process of harmful gas generated during blasting operation on the tunnel face by establishing the finite element model of gas turbulent flow and concentration diffusion in the tunnel, and study the spatial-temporal evolution law of CO concentration field under different air pipe layout locations and tunnel excavation methods. The results show that, compared with corner layout, haunch layout, and central layout, the ventilation effect is the best when the air pipes are arranged near the wall at the tunnel vault, and the CO concentration can be reduced to the concentration limit after 588 s of ventilation; compared with the full-face tunneling method and the lower pilot heading method, the benching tunneling method can effectively reduce the retention time of CO near the tunnel face, and the CO concentration on the tunnel face can be reduced to the standard limit after 326 s of ventilation near the wall of tunnel vault.